Pengembangan Media Pembelajaran Interaktif C-Bonds untuk Mendeteksi dan Mereduksi Miskonsepsi dengan Strategi Conceptual Change Text - Eri Zuimatus Sa'diyah; Sukarmin Sukarmin (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This research aims to analyze the feasibility of C-Bonds interactive media as a detector and reducer of students' misconceptions on chemical bonding material using the Conceptual Change Text Strategy. This research method uses research and development methods that are limited to product trials with research subjects 12 students of class XI MA Roudlotun Nasyiin. The instruments used in this research include validation sheets, observation sheets and student responses, and three tier diagnostic test. The data analysis technique of this research used descriptive quantitative. The results showed the percentage of content validation was 92.59% in the very valid category and the construct validation was 91,44% in the valid category. The results of the percentage of the questionnaires response was 91.31% and the result of the observations was 95,39% both of which were included in the very practical category. The result of the percentage shift of students' misconceptions was 87.95% with the very effective category. Judging from the results of the validation, practicality, and effectiveness, C-Bonds interactive media can be said to be feasible to detect and reduce student misconceptions.